EU political and legal keyword: sovereignty - Aldrovandi, Mattia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The goal of this paper is to briefly analyse the historical movements that led to the emergence and the development of the concept of sovereignty and, secondly, to spread some light on the conceptual miasma which accompanied the development of such protean construct up to the present day. Finally, this paper will take in exam the status of sovereignty in relation to the current European political landscape, namely the European Union.
Keywords: European Union; sovereignty